2017
DOI: 10.18632/oncotarget.22117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metformin use on survival in prostate cancer: a systematic review and meta-analysis

Abstract: BackgroundMetformin has been implicated to reduce the risk of prostate cancer (PCa) beyond its glucose-lowering effect. However, the influence of metformin on prognosis of PCa is often controversial.ResultsA total of 13 cohort studies encompassing 177,490 individuals were included in the meta-analysis. Data on overall survival (OS) and cancer-specific survival (CSS) was extracted from 8 and six studies, respectively. Comparing metformin users with non-metformin users, the pooled hazard ratios (HRs) for OS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…Metformin is commonly used for patients with diabetes mellitus, and a retrospective large‐scale study showed that metformin use in patients with prostate cancer receiving androgen deprivation therapy was associated with improved oncological outcomes . Furthermore, metformin use had a trend to improve survival for prostate cancer patients in meta‐analysis . Metformin was reported to reduce prostate cancer growth prominently under HFD, acting through the modulation of several tumoral‐associated processes in a xenograft model of human cell lines using immunodeficient mice .…”
mentioning
confidence: 99%
“…Metformin is commonly used for patients with diabetes mellitus, and a retrospective large‐scale study showed that metformin use in patients with prostate cancer receiving androgen deprivation therapy was associated with improved oncological outcomes . Furthermore, metformin use had a trend to improve survival for prostate cancer patients in meta‐analysis . Metformin was reported to reduce prostate cancer growth prominently under HFD, acting through the modulation of several tumoral‐associated processes in a xenograft model of human cell lines using immunodeficient mice .…”
mentioning
confidence: 99%
“…In contrast, the same study found that the use of sulphonylureas or insulin was associated with 1.49‐ (95% CI: 1.00‐2.23) and 2.58‐fold (95% CI: 1.72‐3.90) higher risks of breast cancer death. Other recent meta‐analyses have also reported a beneficial effect of metformin on incidence and/or survival in various cancers including liver, prostate cancer, colorectal cancer, endometrial cancer and pancreatic cancer …”
Section: Resultsmentioning
confidence: 90%
“…53 In contrast, the same study found that the use of sulphonylureas or insulin was associated with 1.49-(95% CI: 1.00-2.23) and 2.58-fold (95% CI: 1.72-3.90) higher risks of breast cancer death. Other recent meta-analyses have also reported a beneficial effect of metformin on incidence and/or survival in various cancers including liver, 54,55 prostate cancer, 56 colorectal cancer, 57,58 endometrial cancer 59,60 and pancreatic cancer. 61 Although some observational studies show clear evidence of survival benefit in cancer patients with diabetes receiving metformin, the situation is by no means clear.…”
Section: Potential Use In Oncologymentioning
confidence: 89%
“…It has been previously demonstrated that inhibitors targeting mitochondrial oxidative phosphorylation such as biguanides induce death of RCC cells and may become therapeutic options to overcome the disastrous consequences of SOD2abundance in RCC cells [9]. Furthermore, the antitumor effect of biguanides like metformin in patients with diabetes has been demonstrated in several carcinomas [23][24][25][26][27]. In order to target tumor cell mitochondria, applying biguanides to replacement therapy or drug repositioning should be proposed for patients with SOD2-abundant RCC for maintenance phase treatments after primary surgery debulking numbers of RCC cells.…”
Section: Discussionmentioning
confidence: 99%